Pengembangan Buku Ajar Teori Graf untuk Mahasiswa Pendidikan Matematika - Ratih Puspasari; Tutut Suryaningsih (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
One effort to improve the quality of mathematics learning is to provide teaching materials that are appropriate to the classroom situation. The purpose of this development research is to produce teaching materials in the form of Graf Theory textbooks which are expected to help improve student activity. The research method used follows the design of the ADDIE model. The results of the study are that the draft Theory Graf textbook prepared can be used as a textbook. This can be done because all validators state that the quality of the textbooks that are made includes good and very good categories. Furthermore, by paying attention to the comments, input / suggestions from the validators, the teaching book is revised again so that it becomes more perfect and finally can be legalized into a textbook ready for use by Mathematics Education lecturers and students as one of the learning resources for graph theory courses. Besides that the resulting textbooks are expected to overcome the lack of teaching materials available at STKIP PGRI Tulungagung Mathematics Education Study Program.